Elementos eslavos en el caló - Guillén Monje, Gonzalo (Eslavística Complutense, 2003)
This item treats about the elements of the Slavonic languages that appear in the Romany variaty of the Iberian Peninsula. It is also carried out a comparation between the Spanish gypsy dialect and the Russian jargon. It’s paid attention in the coincidences of both languages thanks to added words which hayo a same origin, this is the lndostanic Paninsula languages.
Keywords: Slavonic languages; Spanish gypsy language; Romany; Russian jargon